Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve 5(g-2)+g = 6(g-4)

Sagot :

5(g-2)+g = 6(g-4)
5g-10+g = 6g-24
6g-10=6g-24
contradiction
Scryt
[tex]5(g-2)+g = 6(g-4)[/tex]
[tex]5g-10+g = 6g-24[/tex]
[tex]6g-10 = 6g-24[/tex]
[tex]6g-6g=-24+10[/tex]
[tex]0=-14[/tex]
[tex]0 \neq -14[/tex]